Variasi Anatomi Jumlah Tendon Musculus Extensor Antebrachii di Laboratorium Anatomi Fakultas Kedokteran Universitas Hang Tuah Surabaya - Yoefan Faishal Islam (HANG TUAH MEDICAL JOURNAL, 2017)
Background. Knowledge of anatomy and variations on the dorsum of the hand extensor tendon is important to anatomist, also for the surgeon's. The hand is one of the most frequently injured organ. Contraction of the extensor muscles synergistically together with flexor muscles is important for grasping the different objects in life. Because of that research is needed to minimize errors in surgery. Goal. To determine the number of anatomical variations of the forearm extensor muscles and tendons Method. This research is descriptive quantitative approach that has been carried out in the Laboratory of anatomy Medical Faculty of Hang Surabaya in August 2016. Sampling using purposive sampling with samples from wet mount preparations hand totaling 12 number of cadaveric samples. Results and Conclusion. Variations in the number of musculus extensor digitorum tendon 1 totaling 1 there were 10 (90.9%), numbered to 2 is 1 (9.1%). The number of musculus extensor digitorum tendon 2 totaling 1 there were 10 (83.3%), which numbered to 2 are 2 (16.7%). Number of musculus extensor digitorum tendon 3 totaling 1 is 1 (8.3%), which numbered to 2 are 9 (75%) and numbered to 3 is 2 (16.7%). Number of musculus abductor tendon policis longus (APL) The number 1 there were 11 (91.7%) while totaling 3 is 1 (8.3%). Number of musculus extensor tendon policis brevis (EPB) are all totaling 1. Number musculus extensor tendon policis longus (EPL) numbering 1 there were 11 (91.7%), which numbered to 2 is 1 (8.3%). Variations in the amount of musculus extensor tendon digiti minimi (EDM), which numbered to 1 are 3 (25%), which numbered to 2 are 9 (75%). Where the factor that influence in this research is the age and race